Thermal Comfort At The Street Corridor Around Public Places, Case Study Alun-Alun Malang City - Erna Winansih; Antariksa Antariksa; Surjono Surjono; Amin Setyo Leksono (Journal of Islamic Architecture, 2016)
Malang as the second largest city in East Java province become crowded recently. The congestion almost happens everyday. The scenery of the street corridor is full of iron stacks. It is said that Malang city is less comfortable and less walkable. The decrease of this environment encourages to conduct the study (Q.S. 16:90, Q.S. 96:1-5, Q.S. 30:41). The study aimed to analyze the thermal comfort at pedestrian ways around Malang city squares, the street corridor of Merdeka Alun-Alun (MAA) and the Tugu Alun-Alun (TAA). The temperature and relative humidity were measured by multinorm instrument. The THI (Temperature Humidity Index) method was used to analyze the thermal comfort. The results showed that the THI average at TAA (27) were more comfortable than at MAA (27,5). The south side of the MAA corridor became the most comfortable with the THI value of 26,4, which the side covered by trees canopy (Q.S. 7:58). It needs to conduct next research (Q.S. 13:11), because of the change of the activities at these street corridors.